1982
DOI: 10.1016/0306-4522(82)90087-2
|View full text |Cite
|
Sign up to set email alerts
|

Efferent connections of dorsal and ventral agranular insular cortex in the hamster, Mesocricetus auratus

Abstract: The anterior portion of rodent agranular insular cortex consists of a ventral periallocortical region (AIv) and a dorsal proisocortical region (AId). Each of these two cortical areas has distinct efferent connections, but in certain brain areas their projection fields are partially or wholly overlapping. Bilateral projections to layers I, III and VI of medial frontal cortex originate in the dorsal agranular insular cortex and terminate in the prelimbic, anterior cingulate and medial precentral areas; those ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
74
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(82 citation statements)
references
References 62 publications
8
74
0
Order By: Relevance
“…The distribution of putative first-order (directly projecting) PRV-positive neurons within the thalamus of rats infected for 2 days that project to either the insular or cingulate cortices in this study are largely consistent with previous monosynaptic tracing studies (2,9,23,28,43,(51)(52)(53)68). The majority of the overlapping regions of the thalamus that project to both the insular and cingulate cortex are localized to the midline thalamic region (2,9,28,43,(51)(52)(53)68).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The distribution of putative first-order (directly projecting) PRV-positive neurons within the thalamus of rats infected for 2 days that project to either the insular or cingulate cortices in this study are largely consistent with previous monosynaptic tracing studies (2,9,23,28,43,(51)(52)(53)68). The majority of the overlapping regions of the thalamus that project to both the insular and cingulate cortex are localized to the midline thalamic region (2,9,28,43,(51)(52)(53)68).…”
Section: Discussionsupporting
confidence: 89%
“…The emotional aspects of thirst therefore reflect the arousal and affect associated with the generation of thirst and the motivation to obtain satiation. Thirst has been considered in many physiological studies (36,48,69,70); however, the effector regions responsible have only been alluded to (18,19,21,48) and therefore require further investigation.The thalamus has been implicated as having a role in the translation of viscerosensory information into signals of arousal and affect (9, 47, 56, 71) through intricate thalamocortical connections (9,23,28,43,(51)(52)(53)68). Two cortical regions implicated in the emotional aspects of thirst, the activity of which is altered by hyperosmotic stimulation or dehydration, are the insular and cingulate cortex (17,20,21,48,54).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Those VP functions may arise partly from its connection with other reward structures such as amygdala (Galaverna et al 1993;Napier 1992), orbitofrontal and insular cortex (Reep and Winans 1982;Zahm 2006), ventral tegmentum, and parabrachial nucleus (Groenewegen et al 1993;Grove 1988a,b;Kalivas et al 1999;Mitrovic and Napier 1998;Napier and Mitrovic 1999). VP also acts as the chief target for efferent projections from the nucleus accumbens, which itself codes reward information (Gulley et al 2002;Peoples et al 2004), and serves as a centripetal final common output path for mesocorticolimbic circuits (Groenewegen et al 1999;Usuda et al 1998;Zahm 2006).…”
Section: Circuitry Mediating Hedonic Codingmentioning
confidence: 99%
“…The function of the amygdala would be to synthesize the various stimulus inputs from the environment and then signal to the PAG according to the degree of threat represented to the organism (LeDoux, 1994, LeDoux, et al, 1988, McNaughton and Corr, 2004. A series of retrograde studies revealed that the projections to the PAG arise predominantly from the medial prefrontal cortex wall and a few selected orbital/anterior insular prefrontal cortex regions (Floyd, et al, 2000, Reep andWinans, 1982). In addition, injections of anterograde tracers into each PAG-projecting prefrontal region revealed distinct columnar patterns in the PAG.…”
Section: The Defence Circuit Of the Pagmentioning
confidence: 99%